Immunization with Neospora caninum profilin induces limited protection and a regulatory T-cell response in mice - Mansilla, Florencia Celeste (2015)
Profilins are actin-binding proteins that regulate the polymerization of actin filaments. In apicomplexan parasites, they are essential for invasion. Profilins also trigger the immune response of the host by activating TLRs on dendritic cells (DCs), inducing the production of pro-inflammatory cytokines. In this study we characterized for the first time the immune response and protection elicited by a vaccine based on Neospora caninum profilin in mice. Groups of eight BALB/c mice received either two doses of a recombinant N. caninum profilin expressed in E. coli. (rNcPRO) or PBS, both formulated with an aqueous soy-based adjuvant enriched in TLR-agonists. Specific anti-profilin antibodies were detected in rNcPRO-vaccinated animals, mainly IgM and IgG3, which were consumed after infection. Splenocytes from rNcPRO-immunized animals proliferated after an in vitro stimulation with rNcPRO before and after challenge. An impairment of the cellular response was observed in NcPRO vaccinated and infected mice following an in vitro stimulation with native antigens of N. caninum, related to an increase in the percentage of CD4+CD25+FoxP3+. Two out of five rNcPRO-vaccinated challenged mice were protected; they were negative for parasite DNA in the brain and showed no histopathological lesions, which were found in all PBSvaccinated animals. As a whole, our results provide evidence of a regulatory response elicited by immunization with rNcPRO, and suggest a role of profilin in the modulation and/or evasion of immune responses against N. caninum.